The Position of Naqshabandi Order in The Islamic Law by Shaykh Islam Wan Sulaiman Wan Sidek (D.1354h/1935m) - M Khairi Mahyuddin (Teosofia: Indonesian Journal of Islamic Mysticism, 2020)
Sufi Order in the Malay World at 19thcentury is misunderstood as deviant teaching from Islam by some of Malay Muslim society.  Reflecting on this, Wan Sulaiman bin Wan Sidek, a shaykh Islam and Malay Sufi scholar at 19th, he played a crucial role in clarifying this issue properly in his Malay Jawi script epistles, namely Fakihah Janiyyah fi Bayan Ma’rifah al-Ilahiyyah al-Mutabaqah Li’ayan al-Shari’ah al-‘Aliyyah and Mizan al-‘uqala wa al-Udaba’. However, some studies from contemporary Malay contested his Sufi's thought, particularly Naqshabandi Order’s position in Islamic law. This study aims to expose Wan Sulaiman’s understanding and justification in Sufis Order, specifically Naqshabandi Order in shariah. This study is a historical and textual analytical study. The finding of this study indicates that Wan Sulaiman’s idea is clear and has strong argumentation from the authentic Sufi sources that show the Sufi Order is legal and has a good position and core teaching in Islamic law.